Stres Psikologis pada Perempuan Dewasa Awal: Studi Kasus Konflik Interpersonal Akibat Campur Tangan Ibu Sambung - Annisa Alda Arrumdias; Tatik Meiyuntariningsih (Journal of Health, Medical, and Psychological Studies, 2026)
Interpersonal conflict within family relationships may contribute to psychological stress, particularly among young adult women experiencing challenges in identity development, autonomy, and emotional adjustment. This study aimed to describe the dynamics of psychological stress experienced by a young adult woman due to interpersonal conflict with her stepmother using a descriptive case study approach. The participant was a 21-year-old female who experienced emotional distress related to prolonged family conflict. Data were collected through observation, semi-structured interviews, and psychological assessments using DASS-42, SSCT, Draw-A-Person, and BAUM tests. The findings revealed that the participant experienced very severe stress characterized by emotional distress, negative thoughts, mood changes, concentration difficulties, and withdrawal tendencies. The conflict was perceived as a major stressor that triggered maladaptive appraisal and dominant emotion-focused coping strategies. Cognitive restructuring and imagining new responses were identified as relevant interventions to improve emotion regulation and adaptive coping strategies.